Transgenic Expression of Tobacco mosaic virus Capsid and Movement Proteins Modulate Plant Basal Defense and Biotic Stress Responses in Nicotiana tabacum - G. Conti; M. C. Rodriguez; C. A. Manacorda; S. Asurmendi (Molecular Plant-Microbe Interactions, 2012)
Plant viruses cause metabolic and physiological changes associated with symptomatic disease phenotypes. Symptoms involve direct and indirect effects, which result in disruption of host physiology. We used transgenic tobacco expressing a variant of Tobacco mosaic virus (TMV) coat protein (CPT42W) or movement protein (MP), and a hybrid line (MP×CPT42W) that coexpresses both proteins, to study the plant response to individual viral proteins. Findings employing microarray analysis of MP×CPT42W plants and silenced mp×cpT42W* controls revealed that altered transcripts were mostly downregulated, suggesting a persistent shut-off due to MP×CPT42W expression. Next, we showed that MP triggered reactive oxygen species (ROS) accumulation, reduction of total ascorbate, and expression of ROS scavenging genes. These effects were enhanced when both proteins were coexpressed. MP and MP×CPT42W plants showed increased levels of salicylic acid (SA) and SA-responsive gene expression. Furthermore, these effects were partially reproduced in Nicotiana benthamiana when GMP1 transcript was silenced. CPT42W seems to be playing a negative role in the defense response by reducing the expression of PR-1 and RDR-1. MP and MP×CPT42W transgenic expression promoted a recovery-like phenotype in TMV RNA infections and enhanced susceptibility to Pseudomonas syringae and Sclerotinia sclerotiorum. The individual effects of viral proteins may reflect the ability of a virus to balance its own virulence.